Therapeutic options to treat mustard gas poisoning - Review - Mehrdad Rafati-Rahimzadeh; Mehravar Rafati-Rahimzadeh; Sohrab Kazemi; Ali Akbar Moghadamnia (Babol University of Medical Sciences, 2019)
Among the blistering (vesicant) chemical warfare agents (CWA), sulfur mustard is the most important since it is known as the "King of chemical warfare agents". The use of sulfur mustard has caused serious damages in several organs, especially the eyes, skin, respiratory, central and peripheral nervous systems after short and long term exposure, incapacitating and even killing people and troops. In this review, chemical properties, mechanism of actions and their effects on each organ, clinical manifestations, diagnostic evaluation of the actions triage, and treatment of injuries have been described.